Serverless cloud computing framework for smart grid architecture - Dash, Shitikantha; Dash, Dipak Kumar (2016 IEEE 7th Power India International Conference (PIICON), 2016)
Additional digital layer is an important aspect in the Smart grid architecture. We gather the data using this layer and the whole grid is controlled accordingly. Energy cost can be estimated and the demand can be predicted. Estimation of health issues of electrical equipment can be done from the control room by gathering the data from remote locations. In the case of computer-aided digital relay model if we choose the pilot relay action by remote data then that would be the good application of this digital layer. In this paper, we have suggested an alternative method- to gather and analyze the remote data using the serverless cloud computing framework. The prime objective is to design a cheaper and technically easier simulation strategy with this new framework. At the end, we have tried to create a mathematical model to estimate the cost and quality of service. The system is simulated using MATLAB, Amazon Web Service (AWS) products and a batch program.